"Raus aus der Haut": Division and Identity in Current German Cinema - Hester Baer; Lutz Koepnick (GDR Bulletin, 1998)
A Report from the "48. Internationale Filmfestspiele Berlin," February 11-22, 1998 Notes 1. Gerhard Schulze, Die Erlebnisgesellschaft: Kultursoziologie der Gegenwart (Frankfurt/M.: Campus, 1992). For a critical discussion of Schulze's terms, see Axel Honneth, Desintegration: Bruchstücke einer soziologischen Zeitdiagnose (Frankfurt/M.: Fischer, 1995). 2. Homi K. Bhabha, The Location of Culture (London: Routledge, 1994) 70. 3. Leslie A. Adelson, Making Bodies, Making History: Feminism and German Identity (Lincoln: Nebraska UP, 1993) 36.